2020
DOI: 10.1021/acsmacrolett.0c00608
|View full text |Cite
|
Sign up to set email alerts
|

Position-Dependent Diffusion Dynamics of Entangled Polymer Melts Nanoconfined by Parallel Immiscible Polymer Films

Abstract: The morphological structure and dynamics of confined polymers adjacent to the polymer–polymer interface have a profound effect on determining the overall physical properties of polymer blends. We measured the diffusion dynamics of poly­(methyl methacrylate) (PMMA) melts confined between polystyrene (PS) layers using neutron reflectivity. Combinations of various thicknesses of PMMA and deuterated PMMA (dPMMA) allowed us to experimentally reveal the nonmonotonic behavior of polymer mobility near the PS–PMMA inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
(75 reference statements)
1
3
0
Order By: Relevance
“…As the ring monomer approaches the film surface, m increases by up to 40%, suggesting that ring monomers are quite mobile at the film surface. The presence of such mobile surfaces is consistent with previous studies. This suggests that the lateral diffusion of the relatively flexible ring chain at the film surface would be facilitated due to the high mobility at the film surface.…”
Section: Results and Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As the ring monomer approaches the film surface, m increases by up to 40%, suggesting that ring monomers are quite mobile at the film surface. The presence of such mobile surfaces is consistent with previous studies. This suggests that the lateral diffusion of the relatively flexible ring chain at the film surface would be facilitated due to the high mobility at the film surface.…”
Section: Results and Discussionsupporting
confidence: 91%
“…The transport of polymer chains in thin polymer films has been an issue of interest because the transport of thin polymer films is different from that of bulk polymer melts. There were many reports that the mobility of chains increased at the film surface compared to that at the film center. In addition, Si et al showed that the density of entanglements of linear chains was reduced at the surface of films. Also, it is known that the structure of ring chains at the film surface is different from that in bulk melts. , Therefore, one may expect that the ring diffusion in linear polymer chain films should depend on the spatial arrangement, the extent of threading, the compressed ring conformation at the surface, and the mobile film surface.…”
Section: Introductionmentioning
confidence: 99%
“…Because DLS, XPCS, and SPT require both low T g ( T g < T room ) matrices or liquid environments and very dilute systems, these methods are unable to explore many industrially relevant conditions of PNCs with crowded, polydisperse, strongly attractive, or nonspherical nanoparticles . On the smallest length scales (nm), neutron reflectivity (NR) has been used to probe diffusion of soft nanoparticles and polymer tracer diffusion in polymer melts. Polymer diffusion studies have also used elastic recoil detection (ERD), formerly known as forward recoil spectroscopy (FRES), to determine self-diffusion coefficients, , but similar to RBS, ERD is becoming less accessible and probes a limited length scale.…”
Section: Introductionmentioning
confidence: 99%
“…Supported polymer films exhibit physical properties that significantly deviate from bulk polymers, such as glass transition temperature, [1][2][3][4][5][6][7] physical aging, 7-14 crystallization, 7,[15][16][17][18][19][20] and diffusion, [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] because of confinement-induced alterations in the conformation and mobility of polymer chains near interfaces and free surfaces. The effects of confinement on the physical properties and dynamics of polymer films, as well as the underlying reasons, have been the focus of much scientific and technological research, owing to their potential applications in microelectronics, sensors, membranes, and coatings.…”
mentioning
confidence: 99%